An Analysis of the Students’ Difficulties in TOEFL Prediction Test of Listening Section - Fitria, Tira Nur (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
This study is to know the students’ difficulty in doing the TOEFL prediction test, especially the listening section in ITB AAS Indonesia. This study uses descriptive qualitative research by using a questionnaire. The result shows that the students’ difficulty in doing TOEFL listening both external and internal factors. In external factors, include: 1) the speaker's accent (75.5 %), 2) the speakers’ speed (75.9 %), 3) the speakers’ intonation/emphasis (73 %), 4) the speakers’ pause in pronouncing a sentence (70.3 %), 5) the choice of words and foreign terms conveyed by the speaker (71 %), 6) the sentence structure conveyed by the speaker is too complex (54.8 %), 7) audio interruption causes the audio sounds less/unclear (54.8 %). In internal factors, include: 1) 64.3 % of students do not have previous experience doing TOEFL test, 2) 58.5 % of students have lack of practice in TOEFL listening, 3) 78.8 % of students have limited time in doing TOEFL listening test, 4) 62.2 % of students feel a lot of listening questions which consist of 50 questions, 5) 76.2 % of students do not have hearing impairment in listening, 6) 51 % of students have memory limitations when listening to TOEFL, 7) 48.1 % of students lack of motivation and enthusiasm, 8) 52.7 % of students lack of concentration or focus, 9) 53.5 % of students have limited mastery of foreign/unfamiliar vocabularies, 10) 47.3 % of students feel boredom when listening, 11) 56 % of students feel easily distracted by sounds or other things, 12) 51 % of students tend to translate any foreign vocabularies when listening, 13) 52.7 % of students have trouble catching or finding keywords, 14) 44.4 % of students are busy along with other activities when listening, such as playing writing instruments, taking notes or doing other things. Keywords: Listening, TOEFL, TOEFL Prediction Test